Direct extraction and detection of malachite green from marine sediments by magnetic nano-sized imprinted polymer coupled with spectrophotometric analysis. (September 2020) - Zhao, Min; Hou, Zonghao; Lian, Ziru; Qin, Dan; Ge, Changzi
Abstract: This research describes the application of magnetic molecularly imprinted nano-sized polymers (MMIPs) for the selective extraction and fast detection of malachite green (MG) from marine sediment samples followed by UV–Vis spectrophotometry. The novel material was prepared by surface imprinting using methacrylic acid as the functional monomer for fixing the template molecules. The polymers obtained at each step were thoroughly studied by transmission electron microscopy, FTIR spectroscopy and thermogravimetric analysis. Simultaneously, the adsorption performances of the resulting nanoparticles were analysed in detail and an excellent affinity with the MG was revealed. Further, the main parameters of magnetic molecular imprinted solid-phase extraction (MMIP-SPE) were screened via multivariate optimization methods. The magnetic nanoparticles were used as special adsorbents to directly extract MG from crude marine sediment extracts. The developed method exhibits satisfactory recoveries from the spiked samples, ranging from 80.40 to 92.96% with an RSD of less than 5.18% (n = 3). Graphical abstract: Unlabelled Image Highlights: Magnetic imprinted nano-particles for malachite green (MG-MMIPs) were prepared. The MG-MMIPs showed remarkable adsorption capacity, kinetics and selectivity. A magnetic SPE procedure for MG was developed by multivariate optimization. Marine sediments were fastly analysed by magnetic SPE coupled with UV–Vis spectrophotometer.